Wave Forces on Linear Arrays of Rigid Vertical Circular Cylinders in Regular Waves - ., VJ Kurian, AA Sebastian, AM Al-Yacouby, MS Liew, VG Idichandy (2014)
The present investigation aims to experimentally determine the variation of forces and force coefficients acting on circular cylinders, which are arranged in a linear array along the direction of the waves. Most commonly used structural and non-structural elements in the construction of offshore platforms are circular cylindrical members. In many cases, these members are found in very close neighbourhood of each other, thus modifying the surrounding flow and wave forces acting on them. Model tests were conducted in the wave tank on a maximum of four cylinders of the same diameter. A reasonable scale factor was chosen considering the pertinent factors such as water depth, wave generating capability and accuracy of measurements. The cylinders were installed inside the wave tank as vertical cantilevers fixed at the top. Wave forces acting on the cylinders were measured using special wave force sensors exclusively designed and fabricated for the present project, while the wave profiles were recorded using wave probes installed in the wave basin. The results confirmed the presence of a force shielding effect on the trailing cylinders by the leading cylinders with few exceptions. The findings also substantiated the significant modification of the forces on cylinders when they are present in a linear array. A common practice adopted for the design of offshore platforms was identified with a possibility of underestimating the wave forces acting on the cylindrical elements. In many cases, the experimentally computed hydrodynamic force coefficients were found to be lower than the standard values adopted by various design codes. These findings portray the significance of the present work in achieving economy in the design of jacket platforms and risers.